Political, Economic, Historical, Social and Spiritual Life during the Reign of Amir Temur - Kholmamatovna, Jabborova Qizlargul (International Journal on Human-Computing Studies, 2022)
The article examines the spiritual heritage left by our ancestors, in particular, the wonderful progressive ideas of Amir Temur, necessary for all spheres and for all periods.